(untitled) (Research, Society and Development, 2024)
The use of active teaching-learning methodologies is an innovative method, using real or simulated experiences, aiming to create conditions to solve, in different contexts, the challenges arising from the essential activities of social practice. Thus, the general objective of this study is to investigate in the literature the importance/effectiveness of active teaching-learning methodologies in Higher Education (Undergraduate and Postgraduate). Based on an integrative review, a bibliographic survey was carried out in magazines and periodicals indexed in the Scientific Electronic Library Online (SciELO), CAPES and Google Scholar journals, totaling 08 articles. Based on the works analyzed, it is notable that there is currently a wide discussion about the importance of using active teaching-learning methodologies, especially with regard to Higher Education. There are various active methodologies that have methods with different properties in their applications, each with its own peculiarities. In the sample collected, the use of active teaching-learning methodologies was observed mainly in the Undergraduate scenario, with emphasis on the Health area (Physical Education, Psychology, Medicine, Biomedicine, Speech Therapy, Physiotherapy, Radiology and Occupational Therapy courses). It is concluded that there are several benefits, effectiveness/efficiency of using active methodologies, while there are still various challenges/difficulties in using them, whether on the part of teachers (such as lack of training/lack of instruction, or even problems involving lack of planning) or even the lack of motivation of the students themselves.